Biomarkers used in the diagnosis and prognosis of gastric cancer in young patients: a scientometric analysis - Azbergenov, Nurbek Kozhakhmetuly; Akhmetova, Saule Zhumabaevna; Nurulla, Talshyn Amirkhanovna; Kaliev, Abdiraman Rsalievich; Ramankulova, Aigul Bulatovna; Tulyayeva, Anar Balkashevna; Kereeva, Nurgul Meirimovna (Frontiers in Medicine, 2025)
IntroductionGastric cancer in young people is a global health burden, although it is less common than in other age groups. The use of biomarkers is developing in the diagnosis, treatment selection and prognosis of gastric cancer in young patients. In this bibliometric analysis we aim to evaluate the progress of this knowledge, trend topic development and scientific teams and countries involvements in the topic of biomarkers role in gastric cancer in young patients.MethodsThe data were obtained from Scopus (536 publications) for the period 1993–2024, all relevant metadata were analyzed using RStudio and Biblioshiny package to perform global trends and hotspots analysis.ResultsPublication trends show a constant increase in interest in gastric cancer biomarkers used in the diagnosis and prognosis of gastric cancer in young patients (7.71% per year). The leading countries were China, USA, and Japan, between which there is strong and sustained collaborations. International co-authorship is relatively low (19.4%). The most prolific research centers were Sungkyunkwan University, Sun Yat-sen University, and Fudan University. The most productive researchers were Zhang X., Wang Y., and Li Y. Keywords analysis showed an increase in mentions of topics related to diagnostics (biomarkers, immunohistochemistry), personalized medicine and prognosis.ConclusionBibliometric analysis of more than three decades research articles on gastric cancer biomarkers in young patients showed a steady increase, with strong contributions from leading countries and institutions, highlighting the growing focus on diagnostics, personalized medicine, and prognosis.